A Numerical Study on the Effect of Structured Multizone Meshing on Air-Foil Aerodynamics at Low Angles of Attack - Ramadhan, Andri; Putri, Maharani (CV Raskha Media Group, 2025)
This study presents a numerical analysis of airfoil aerodynamic characteristics at low angles of attack using a structured multizone meshing approach. The computational model was developed in ANSYS Workbench, with simulations conducted using ANSYS Fluent on a two-dimensional airfoil enclosed within a far-field domain. The mesh configuration consists of approximately 540,000 elements and 541,000 nodes, achieving a maximum skewness below 0.26, which indicates high mesh quality and numerical stability. Steady-state simulations were performed for angles of attack of −5°, 0°, 5°, and 10° to evaluate lift and drag behaviour, as well as pressure and velocity distributions around the airfoil surface. The numerical results show a consistent increase in lift coefficient with increasing angle of attack, accompanied by a corresponding rise in drag coefficient. At moderate angles of attack, particularly around 5°, the airfoil demonstrates an optimal aerodynamic performance with a favourable lift-to-drag ratio. These findings highlight the capability of structured multizone meshing to accurately capture key aerodynamic trends while maintaining computational efficiency. The results confirm that this meshing strategy is suitable for preliminary aerodynamic analysis and early-stage design of airfoil-based applications, such as small-scale wind turbine blades operating under low to moderate inflow conditions